An Investigation Into the Relationship Between Onset Age of Musical Lessons and Levels of Sociability in Childhood - Kawase, Satoshi; Ogawa, Jun’ichi; Obata, Satoshi; Hirano, Takeshi (Frontiers in Psychology, 2018)
Previous studies have suggested that musical training in childhood is beneficial for sociability. However, it remains unclear how age of onset of group music lessons is associated with the late sociability of children from a long-term perspective. This study investigated associations between group music lessons conducted at a music school and children’s levels of sociability by focusing on the age of onset of the lessons. We conducted a survey of 276 children aged 4–5 years (M = 58.5 months) and 6–7 years (M = 82.7 months) who commenced music lessons at ages 1, 2, 4, and 6 years. We found that (1) the empathy scores of children aged 6–7 years who began lessons when 1-year-old were greater than those who began lessons when 4-years-old, (2) the communication scores of children aged 4–5 years who began lessons when 1-year-old were greater than those who began lessons when older than 1 year, and (3) the empathy and extraversion scores were high in those aged 6–7 years who began lessons in that age range. The results suggest that early onset of music lessons could positively influence children’s sociability; in contrast, after about age 7 years, children who already had high sociability may be more inclined to select group music lessons. By focusing on the impact of regular group music lessons from a very young age on later levels of sociability, these results further elucidate the effects of musical lessons. In sum, participation in group music lessons 2–4 times per month can be effective social training for very young children and foster their later sociability.